Digitalization of Accounting Profession: A Decade of Bibliometric Analysis - Awang, Yunita; Nasir, Noor Emilina Mohd; Taib, Azuraidah; Shuhidan, Shazalina Mohamed; Ifada, Luluk Muhimatul (Advances in Social Sciences Research Journal, 2024)
The Fourth Industrial Revolution (IR4.0) has altered the global industry requirement to replace human labour with greater digital software and robotic function automation. Similar developments are anticipated in the accounting sector as well, with the shift towards digitalization of the accounting industry. The accounting profession gets more difficult in a digital world because accountants must have greater knowledge of information technology and accounting information systems. To better comprehend this problem, the present study examines the development of research articles on the digitalization of the accounting profession by analysing data from the Scopus database between 2014 and 2023, using bibliometric analysis. The analysis involved looking for patterns in research publications to establish the document type; languages; subject area, publication categories by authors, countries and sources titles, citation metrics and keywords. For this reason, 182 relevant documents were examined in Mac 2024 and the data were analysed using software of Microsoft Excel, VOSviewer, Harzing’s Publish or Perish. This study offers some insights regarding the future development and advancement of the digitalization of the accounting profession topic in the academic literature of Business, Management and Accounting; Economics, Econometrics and Finance; Social Sciences and Decision Sciences, as well as provides helpful information for academics and practitioners looking to analyse and delve deeper within this particular field of research.